Down a sunny dirt road : an autobiography - Berenstain, Stan, 1923-2005 (Random House, 2002)
In alternating chapters Stan and Jan Berenstain, creators of the Berenstain Bears, tell their own stories from early childhood until their marriage, then continue the tale together to the present day.